2003
DOI: 10.1002/nme.830
|View full text |Cite
|
Sign up to set email alerts
|

Parallel multipole implementation of the generalized Helmholtz decomposition for solving viscous flow problems

Abstract: SUMMARYThe evaluation of a domain integral is the dominant bottleneck in the numerical solution of viscous ow problems by vorticity methods, which otherwise demonstrate distinct advantages over primitive variable methods. By applying a Barnes-Hut multipole acceleration technique, the operation count for the integration is reduced from O(N 2 ) to O(N log N ), while the memory requirements are reduced from O(N 2 ) to O(N ). The algorithmic parameters that are necessary to achieve such scaling are described. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Parallel computing is another promising avenue. This has been carried out for the standard 3-D BNM [12], as well as for fast numerical evaluation of integrals in conjunction with MM acceleration [39].…”
Section: Discussionmentioning
confidence: 99%
“…Parallel computing is another promising avenue. This has been carried out for the standard 3-D BNM [12], as well as for fast numerical evaluation of integrals in conjunction with MM acceleration [39].…”
Section: Discussionmentioning
confidence: 99%
“…Instead of trying to convert the domain integral to the boundary, the idea initiated in the work by Greengard et al is to directly evaluate the domain integral, enhanced by employing an acceleration technique such as fast multipole . The calculation is therefore very efficient, it does not approximate the forcing function, and no new unknowns (DRM expansion coefficients) are introduced; in particular, the work in demonstrated that this approach outperformed DRM.…”
Section: Introductionmentioning
confidence: 99%
“…Applications in fluid mechanics seem to be rather sparse compared to other fields. However, there are several possibilities to use the FMA for incompressible flows: potential flow equations as first suggested by Rokhlin (1985), but also Stokes flow (Gómez & Powert 1997;Mammoli & Ingber 2000;Kropinski 2001), vortex methods (Pringle 1994;Scorpio & Beck 1996) and the possibility to come as a component of Navier-Stokes solvers via generalized Helmholtz decomposition (Brown et al 2003). Water-wave computations with multipole-accelerated codes also exist.…”
Section: Introductionmentioning
confidence: 99%